Coronavirus viability in surgical plume and methods for safe disposal: a preclinical model. Issue 1 (18th November 2021) - Chia, Daryl K A; Lim, Zhixue; Ang, Jia Jun; Tambyah, Paul A; Lau, Kelly S H; Ong, Joe; Chow, Vincent T K; Allen, David M; Fung, Javis; Lau, Kenny J X; Luhung, Irvan; Schuster, Stephan C; et al.
Abstract : Smoke generated by cautery devices used during surgery may contain infective particles and may cause transmission of airborne viruses. This study determines whether live viruses are present in surgical smoke and evaluates the effectiveness of several proposed methods of removal so as to improve safety of healthcare workers.